Head first C# - Stellman, Andrew; Greene, Jennifer 1971- (O'Reilly Media, Inc., 2024)
What will you learn from this book? Create apps, games, and more using this engaging, highly visual introduction to C#, .NET, and Visual Studio. In the first chapter you'll dive right in, building a fully functional game using C# and .NET MAUI that can run on Windows, Mac, and even Android and iOS devices. You'll learn how to use classes and object-oriented programming, create 3D games in Unity, and query data with LINQ. And you'll do it all by solving puzzles, doing hands-on exercises, and building real-world applications. Interested in a development career? You'll learn important development techniques and ideas--many who learned to code with this book are now professional developers, team leads, coding streamers, and more. There's no experience required except the desire to learn. And this is the best place to start. What's so special about this book? If you've read a Head First book, you know what to expect: a visually rich format designed for the way your brain works. If you haven't, you're in for a treat. With this book, you'll learn C# through a multisensory experience that engages your mind--rather than a text-heavy approach that puts you to sleep.
Keywords: Microsoft .NET Framework; Microsoft Visual studio; C# (Computer program language); Computer programming; C# (Langage de programmation); Programmation (Informatique); computer programming